Characterization of the ecological spatial structure of the La Mesa sub-watershed formation in metropolitan Manila - Navarra, Nappy L. (Espasyo : Journal of Philippine Architecture and Allied Arts, 2012)
Like other megacities, Metropolitan Manila has a high population density, is heavily-built-up and produces and consumes most of the resources of the country. Given these characteristics, there is a need to analyze its eco-spatial spaces using a framework that is sustainable and viable for its growth and development. The research proposes a watershed-based framework that integrated ecological concepts to analyze its eco-spatial spaces that can be used in the management of the region. the framework utilizes the Geographic Information System (GIS) to generate watershed features and as a system in processing information of the different units in landscape scale. The paper focuses on the La Mesa Sub-watershed formation that forms the head water and is critical in the environmental processes. The La Mesa sub-watershed formation is highly built-up with some sub-watershed units exhibiting significant semi-natural eco-spatial units. The sub-watershed cluster is analyzed in terms of its distribution and eco-spatial units and translated into an environmental management map.